Breeding latitude leads to different temporal but not spatial organization of the annual cycle in a long‐distance migrant. (27th June 2016) - Briedis, Martins; Hahn, Steffen; Gustafsson, Lars; Henshaw, Ian; Träff, Johan; Král, Miroslav; Adamík, Peter
Abstract : The temporal and spatial organization of the annual cycle according to local conditions is of crucial importance for individuals' fitness. Moreover, which sites and when particular sites are used can have profound consequences especially for migratory animals, because the two factors shape interactions within and between populations, as well as between animal and the environment. Here, we compare spatial and temporal patterns of two latitudinally separated breeding populations of a trans‐Equatorial passerine migrant, the collared flycatcher Ficedula albicollis, throughout the annual cycle. We found that migration routes and non‐breeding residency areas of the two populations largely overlapped. Due to climatic constraints, however, the onset of breeding in the northern population was approximately two weeks later than that of the southern population. We demonstrate that this temporal offset between the populations carries‐over from breeding to the entire annual cycle. The northern population was consistently later in timing of all subsequent annual events – autumn migration, non‐breeding residence period, spring migration and the following breeding. Such year‐round spatiotemporal patterns suggest that annual schedules are endogenously controlled with breeding latitude as the decisive element pre‐determining the timing of annual events in our study populations.